The Architecture of Meaning: A Linguistic Analysis of Metaphors and Idioms - Erick Saut Maruli Sihombing; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
This study investigates the cognitive and cultural mechanisms underlying the use of metaphors and idioms to understand their role in constructing linguistic meaning. Using a qualitative approach grounded in linguistic and psycholinguistic analysis, the findings indicate that metaphors involve conceptual mapping between source and target domains, demanding greater cognitive effort, particularly when novel. In contrast, idioms function as fixed expressions stored in memory, allowing rapid retrieval and comprehension when conventionalized. Both reflect cultural values and collective experiences, forming an architecture of meaning that connects individual mental processes with social identity. These findings offer academic implications for linguistic, psycholinguistic, and cultural discourse studies, particularly in understanding the role of figurative language in social interaction.